Hubungan antara Aktivitas Fisik dan Dietary Diversity Score dengan Status Gizi pada Remaja di SMK Negeri 4 Surakarta - Aliva Nimas Mahati; Farida Nur Isnaeni (Yayasan Literasi Sains Indonesia, 2025)
Nutritional status is the condition of the body as a result of food consumption and the use of nutrients. Physical activity and dietary diversity are factors that can effect nutritional status in adolescents. The purpose of this study was to determine the relationship between physical activity and dietary diversity score with nutritional status in adolescents at SMK Negeri 4 Surakarta. This study used a cross-sectonal design with a sample of 61 randomly selected adolescents. Physical activity data were obtained by interview using the IPAQ questionnaire, while dietary diversity intake data were obtained by 3x24 hour recall, namely on 2 weekdays and 1 weekend day on a form containing 9 food groups. The results showed that there was a significant relationship between physical activity and nutrional status in adolescents (p=0,002), but there was no significant relationship between dietary diversity score and nutritional status in adolescents (p=0,0553). This finding indicates that physical activity affects nutritional status in adolescents but dietary diversity cannot represent nutritional status because nutritional status is a representation of long-term consumption patterns.